Research hotspots of irisin in the nervous system: a bibliometric study and visualization analysis via CiteSpace - Jiacheng Wang; Jiacheng Wang; Juan Liu; Juan Liu; Wei Pang; Wei Pang; Wei Pang; Xin Li; Xin Li; Xin Li; Xinping Huang; Shan Wang; et al. (Frontiers in Aging Neuroscience)
ObjectiveTo visually analyze the current status, hotspots, and frontiers of irisin in the nervous system and to provide a reference for future clinical research.MethodsWeb of Science Core Collection (WoSCC), PubMed, Embase, and Cochrane Library databases were searched for studies on the mechanism of irisin on the nervous system published from January 1st, 2012 to April 15th, 2025. CiteSpace 6.4.R1 and Excel 2021 software were used to visualize the knowledge map of the annual number of publications, research institutions, countries, co-cited literature, journal dual map overlays, and keywords of the sample literature.ResultsFour hundred and ninety-eight were included, and the annual number of articles showed an overall upward trend. The institution with the most significant number of articles was the Universidade Federal do Rio de Janeiro (UFRJ), and the country with the most significant number of articles was China. The prevalent keywords were “Exercise,” “Skeletal muscle,” “Neurotrophic factor,” “Expression,” “Alzheimer’s disease,” indicating that the production of irisin and its protective mechanisms for the nervous system are research hotspots in this field. Cluster analysis showed that the research frontier hotspots in this field could focus on three main topics: the functional role and mechanism of irisin, pathological experimental research, and clinical disease research.ConclusionIn recent years, research on irisin in the nervous system has primarily centered on elucidating its neuronal regulatory mechanisms and neuroprotective effects, along with their potential applications in neurological disorders. Future investigations should aim to delineate novel signaling pathways and action mechanisms and systematically identify therapeutic targets for refractory neurological conditions through comprehensive translational studies.